Additive of cow dung weakened the influences of microbial interactions on nitrogen dynamic during composting of rice husks - Zhang, Bin; Meng, Delong; Wang, Xichun; Hu, Jin; Fan, Jianqiang; Li, Xuan; Yang, Zhendong; He, Wei; Zhou, Deying; Cheng, Yiqiang; Li, Jingjing; Zou, Junliang; et al. (Frontiers in Microbiology, 2025)
Rice husk (RH) and cow dung (CD) are two of the most abundant agricultural solid waste. Converting these residues into peat-free substrates through co-composting supports sustainable agricultural development. A 40-day rice husk composting experiment was conducted to assess the effects of cow dung addition on microbial networks and carbon–nitrogen dynamics using 16S rRNA and metagenomic analyses. Furthermore, Furthermore, we prepared seedling substrates from composts of RH alone and RH combined with CD (RHCD), and evaluated their plant growth–promoting effects. The addition of cow dung (CD) to rice husk (RH) composting increased the average temperature from 52.8 °C to 60.1 °C and acted as a pH buffer, maintaining values around 7.4. CD significantly (p < 0.05) enhanced microbial network complexity, as indicated by larger network size and higher average degree, but disrupted the linear correlations between network properties and carbon or nitrate nitrogen contents (p > 0.05). This decoupling suggests that CD weakened the linkage between microbial interactions and carbon or nitrogen biotransformation processes. CD also significantly suppressed (p < 0.05) denitrification-related genes (norB, nir and nar) after the thermophilic phase, implying reduced nitrogen loss during compost maturation. We further found that larger network size or higher average degree reduced the abundance of key genes involved in assimilatory nitrite reduction (e.g., nirBD), while increasing those related to denitrification (e.g., nirK and nirS). Moreover, seedling substrates derived from RH (95.06%) and RHCD (93.21%) composts achieved higher germination rates of Solanaceae crops than the commercial peat-based substrate (81.48%). Germination rate and seedling biomass were positively correlated with dissolved organic carbon (r = 0.820, p = 0.045) and ammonium nitrogen (r = 0.858, p = 0.029), respectively. These findings advance the understanding of microbial interaction regulating carbon and nitrogen cycling during RH composting, and support the sustainable production of peat-free seedling substrates from agricultural waste.